Developing Student-teacher’s Instructional Communication Skills through Teaching Practice: the Attitudes of Mentors - Viršulienė, Kristina (Pedagogika, 2016)
The article analysis the attitudes of mentors to the development of student-teacher’s instructional communication skills through teaching practice. The objective of the research was to reveal the opinion of the mentors about the development of student-teacher’s instructional communication. For that purpose observation was carried out in the natural environment. That helped to reveal the peculiarities of students’ instructional communication skills at teaching practice. Semi-structured interview methods were applied to interview the mentors. The data obtained via the Questionnaire for Mentors allowed to assess the student-teachers’ communication skills, and to identify the key factors for theirs’ professional improvement. The interview data analysis presents mentors’ opinion about the dynamics of the student - teachers’ instructional communication skills at teaching practice, the importance of consultations, student-teachers’ assessment of their instructional skills, needs and possibilities of the skill improvement. It became evident that mentors’ assessment differed according to their work experience. When speaking about students’ assessment, the mentors of considerable experience (more than 5 years of continuous pedagogical work experience) admitted, that they had known students well through observing, communicating, consulting them, when talking to their colleagues they could assess their achievements. While the inexperienced mentors communicated with the student-teachers in a more formal way, they were less prepared to supervise students, help them know themselves and improve their instructional skills. When considering improvement possibilities of teaching practice, all mentors claimed that student-teacher’s professional skills are being gained only by practicing. The mentors stressed that readiness for pedagogical professional practice is very much dependent on student’s ability to participate, to reflect, on willingness for self-knowledge as well as strong professional determination; results of individual practice and consultations with competent professionals.